Determinant Factors of Marital and Job Satisfaction for Working Women in Rural Indonesia - Natasya, Betrin; Matsuoka, Atsushi (Hasanuddin University, 2025)
Investigating marital and job satisfaction is crucial to consider the empowerment and autonomy of women. The first purpose of this study is to analyse the correlation between marital satisfaction, job on farm and off-farm satisfaction of working woman in rural areas in Indonesia. And second purpose is to examine determinant factors of marital and job satisfaction, especially focusing on the decision-making of woman. For the above purpose, I interviewed 70 working women in two villages of Takalar Regency in South Sulawesi. The result showed statistically significant positive correlations between marital satisfaction and both on-farm and off-farm job satisfaction among rural women. This finding suggests a potential spillover effect, where positive experiences in one domain (e.g., marriage) may contribute to satisfaction in another (e.g., work). Furthermore, the data indicate that women with higher levels of decision-making authority experience greater marital and job satisfaction. An educational background was found to be an important factor affecting the marital and job satisfaction of working women in rural areas. The result suggests that increasing the situations in which women are involved in decision- making will increase marital and job satisfaction.